2014
DOI: 10.1017/ice.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Mucosal Barrier Injury Laboratory-Confirmed Bloodstream Infection among Hematology, Oncology, and Stem Cell Transplant Patients

Abstract: Most CLABSIs identified among hematology, oncology, and stem cell transplant patients met MBI-LCBI criteria, and CLABSI prevention efforts did not reduce these infections. Further review of the MBI-LCBI definition and impact is necessary to direct future definition changes and reporting mandates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 21 publications
0
29
2
6
Order By: Relevance
“…A previous study in adult hematology/oncology and stem cell transplant settings has also reported MBI-LCBI events to be associated mainly with neutropenia but without a significant difference in the frequency of neutropenia in MBI-LCBI vs. non-MBI–LCBI cases. 15 However, we found a statistically significant difference in the frequency of neutropenia between MBI and non-MBI LCBI events in pediatric cancer patients. Additional studies in pediatric cancer centers in LMIC that offer allogeneic hematopoietic stem cell transplantation would help to determine whether the absence of transplantation at our center may explain this difference.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…A previous study in adult hematology/oncology and stem cell transplant settings has also reported MBI-LCBI events to be associated mainly with neutropenia but without a significant difference in the frequency of neutropenia in MBI-LCBI vs. non-MBI–LCBI cases. 15 However, we found a statistically significant difference in the frequency of neutropenia between MBI and non-MBI LCBI events in pediatric cancer patients. Additional studies in pediatric cancer centers in LMIC that offer allogeneic hematopoietic stem cell transplantation would help to determine whether the absence of transplantation at our center may explain this difference.…”
Section: Discussioncontrasting
confidence: 51%
“…13 The MBI-LCBI surveillance definition was revised and improved after testing at 94 cancer centers in the U.S. 14 Recently, an oncology center reported using the MBI-LCBI surveillance protocol to separately track MBI and non-MBI events to measure the impact of a CLABSI quality improvement initiative. 15 Because MBI-LCBI cases define a specific at-risk population, the CDC will continue requiring their tracking and reporting. However, MBI-LCBI data may be removed from the main bloodstream infection events tracking metrics by 2016, in which case they will not be included in CLABSI data publicly reported to the U.S. Centers for Medicare and Medicaid Services.…”
Section: Introductionmentioning
confidence: 99%
“…E coli es el patógeno identificado en sangre con mayor frecuencia en bacteremias nosocomiales en la última década, particularmente en la población de pacientes con neoplasias hematológicas asociadas con bacteremia por daño a mucosas. 10,11 En este estudio se reportó un incremento sostenido en la resistencia de 18% en 2003 a 48.6% en 2015, tendencia que también se ha reportado en algunos otros países del mundo, en bacteremia asociada con el cuidado de la salud. [12][13][14][15] El comportamiento de otras bacterias MDR es diverso; se observa un incremento progresivo para K. pneumoniae BLEE y para P. aeruginosa tanto en pacientes con neoplasias hematológicas como en pacientes con tumores sólidos.…”
Section: Discussionunclassified
“…It has been estimated that approximately 40-50% of bloodstream infections in oncologic settings are due to mucosal barrier injury. 89 Therefore, in a recent manual on Central Line-Associated Blood Stream Infections (CLABSI), the definition of Mucosal Barrier Injury-Laboratory Confirmed Bloodstream Infection (MBI-LCBI) has been introduced as reported in Table 1. 7 …”
Section: Central Venous Cathetersmentioning
confidence: 99%